THE CORRELATION BETWEEN VOCABULARY MASTERY AND STUDENTS’ ACHIEVEMENT IN WRITING DESCRIPTIVE TEXT AT THE EIGHTH GRADERS OF SMP NEGERI 3 KOTABUMI IN ACADEMIC YEAR 2020/2021 - Rini Susilowati; Usi Ismayanti; Nurbaiti; Santi; Selvi; Dinda Denada; Arya Ja’wan Darahim (Universitas Muhammadiyah Kotabumi, 2021)
Abstract: This research was intended to explore the phenomenon about the students’ vocabulary mastery can be correlating with their writing achievement. The objectives of this research is to investigate whether there is significant correlation between vocabulary mastery and the students’ achievement in writing descriptive text at the eighth graders of SMP Negeri 3 Kotabumi in academic year 2020/2021. The kind of this research is quantitative research and used correlational research design. The research was followed by 40 students which was established by using proportional random sampling technique. The instrument used in this research were tests and divided into two types of test. The first test was written test and the second test was vocabulary mastery test with multiple choice form. Then, to prove the hypothesis of the research, the researcher analyzed the data by using the formula of pearson product moment correlation and resulted Then, , with the value of was 28,24 and was 2,027. Based on the result of the data analysis above, it can be concluded that Ha is accepted and H0 is rejected, which showed there is significant correlation between vocabulary mastery and the students’ achievement in writing descriptive text at the eighth graders of SMP Negeri 3 Kotabumi in academic year 2020/2021. Keywords: Vocabulary Mastery, Writing Achievement, Descriptive Text.